Analysis and exposure evaluation of cadmium residues in different tissues of portunus and mantis shrimp - NIU Hongxin; LYU Shenliang; FAN Chenyue; JIANG Yuejian; XIONG Xiaoling; TONG Renping (Shanghai yufang yixue, 2023)
ObjectiveTo understand the concentration of heavy metal cadmium and cadmium in portunus and mantis shrimp， and to timely identify food safety problems and potential hazards.MethodsPortunus and mantis shrimp samples from different provinces were collected and categorized based on different regions and locations， and some samples were made from tissue parts. Graphite furnace atomic absorption spectrometry was used to detect cadmium items， the cadmium exposure of portunus and mantis shrimp was evaluated simultaneouslyResultsThe detection rate of cadmium in 124 batches of portunus sold in Shanghai was 100% （124/124）， the detection rate of cadmium in 63 batches of mantis shrimp sold in the market was also 100% （63/63）. The cadmium content varied in different tissue parts， and the cadmium enrichment in hepatopancreas was the highest in the edible parts of portunus and mantis shrimp. The average detection value， 50th percentile value， 95th percentile value of cadmium in the hepatopancreas of portunus accounted for 52.64%， 49.28% and 98.65% of the PTMI， respectively. The average detection value， 50th percentile value and 95th percentile value of cadmium in the hepatopancreas of mantis shrimp accounted for 30.76%， 32.04% and 46.16% of the PTMI， respectively.ConclusionThe average residual levels of heavy metal cadmium in portunus and mantis shrimp are within the safe range.